Impact of COVID-19 on the primary level teaching-learning process in rural India - Vivek, S.; Rangasami, P. (Frontiers in Education, 2024)
Covid 19 outbreak impacts people globally. It is not simply a global health matter; it has a terrible influence on the social life of humans, counting the worldwide education structure and other phases of present social configurations. Therefore, the present study's objective is to identify the impact of COVID-19 on the online education approach in teachers' perceptions. The study performs a mixed research approach for evaluating the teachers' perspectives in the online education system. The quantitative data are collected with the support of a questionnaire from 175 respondents (Public School teachers), and in-depth telephonic interviews are conducted among 25 schoolteachers using a semistructured questionnaire for qualitative data. The quantitative analysis is performed using Statistical Package for Social Sciences (SPSS), and the qualitative analysis is coded and analyzed thematically.The quantitative results show that the Covid-19 pandemic negatively impacted the online teaching method; teachers' adaptation here seems low. In contrast, communication with school leaders is provided a clear view of online teaching methods. The key findings from the qualitative analysis show that the adaptation online education system is complex owing to various struggles. Some institutions facilitate training sessions to teach in a range of adopting the online education system. Finally, the teachers need help making students actively participate in online classes.